Lectotypification of names in Henriettea (Melastomataceae, Henrietteeae) - Brito, Eliete Da Silva; Lima, Laíce Fernanda Gomes De; Baumgratz, José Fernando A.; Viana, Pedro Lage (Phytotaxa, 2019)
The present study proposes the lectotypification of 13 names of Henriettea: H. angustifolia, H. granulata, H. horridula, H. lasiostylis, H. maroniensis, H. spruceana, H. stellaris, H. succosa var. guianensis (= H. ramiflora), Henriettella glazioviana (= Henriettea glabra), Henriettella longistyla (= Henriettea ovata), Henriettella ovata (≡ Henriettea ovata), Melastoma fasciculare (≡ Henriettea fascicularis), and Phyllopus martiusii (≡ Henriettea martiusii).